Preparation of poly(2,5-thienyleneethylene) and poly(2,5-furyleneethylene) by vapor phase pyrolysis of (5-methyl-2-thienyl)methyl benzoate and (5-methyl-2-furyl)methyl benzoate - Lu, YH; Hsu, CS; Chou, CH; Chou, TH (My University, 1996)
The synthesis-of poly(2,5-thienyleneethylene) and poly(2,5-furyleneethylene) by vapor deposition polymerization is presented. (5-Methyl-2-thienyl)methyl benzoate and (5-methyl-2-furyl)methyl benzoate were subjected to vapor phase pyrolysis above 650 degrees C to form 2,5-dimethylene-2,5-dihydrothiophene and 2,5-dimethylene-2,5-dihydrofuran. Upon condensation, both compounds spontaneously polymerize, respectively, at a temperature higher than -25 degrees C to produce poly(2,5-thienyleneethylene) and poly(2,5-furyleneethylene). The obtained poly(2,5-thienyleneethylene) is soluble in chloroform above 60 degrees C. It is a semicrystalline polymer and displays a glass transition at around 25 degrees C and a melting transition at around 160 degrees C. The synthesized poly(2,5-furyleneethylene) is insoluble in tetrahydrofuran, chloroform, dimethylformamide (DMF), and dimethyl sulfoxide (DMSO) at room temperature and only swells in DMF and DMOS above 100 degrees C. Solid-state NMR studies show that the poly(2,5-furyleneethylene) is cross-linked. The poly(2,5-furyleneethylene) is also a semicrystalline polymer exhibiting a glass transition at around 20 degrees C and a melting transition at around 110 degrees C. Solution polymerizations of 2,5-dimethylene-2,5-dihydrothiophene and 2,5-dimethylene-2,5-dihydrofuran were also carried out, respectively, in THF to yield poly(2,5-thienyleneethylene) and poly(2,5-furyleneethylene). Finally, the relative merits for the polymerization of 2,5-dimethylene-2,5-dihydrothiophene and 2,5-dimethylene-2,5-dihydrofuran by both methods are compared.